Capacity Sharing on bundled climate information services (CIS) and climate smart agriculture (CSA) business models and scaling strategies in Africa - Ouedraogo, Mathieu; Kagabo, Desire; Ewell, Hanna; Ogutu, Elizabeth; Abugri Benjamin (2025)
The capacity sharing webinar on bundled climate information services (CIS) and climate-smart agriculture (CSA) business models and scaling strategies in Africa was successfully held in November 2025. The event, jointly organized by the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) and the Forum for Agricultural Research in Africa (FARA), aimed to strengthen institutional and technical capacities of Agricultural Research for Development (AR4D) stakeholders across Africa. Over 697 registrants (including 511 males and 186 females) participated, representing National Agricultural Research Systems (NARS), farmer organizations, academia, NGOs, private sector actors, and policy makers. The sessions focused on bundled CIS/CSA models, the AICCRA scaling framework, and action planning for scaling resilient agricultural innovations across the continent. Participants reported significant improvements in their understanding of scaling strategies and expressed commitment to integrating the lessons into their institutional programs. The training fostered cross-country collaboration and identified pathways for operationalizing the AICCRA Scaling Framework at national and regional levels.